PENGEMBANGAN MEDIA SMART BOX DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN - Nur Adiyah Yuliastri; Rohyana Fitriani; Baiq Shofa Ilhami (UNIVERSITAS PGRI MADIUN, 2021)
Abstract This study aims to develop smart box media and improve cognitive abilities of children aged 5-6 years. This research and development refers to the steps developed by Borg & Gall. The development design is simplified into 6 steps, namely: (1) research and information gathering, (2) planning, (3) developing the initial form of the product, (4) limited trials, (5) product revision, (6) field trials. The subjects of the field trial were 15 children. Data collection uses the validity of expert judgment and observation sheets. The data analysis technique uses a scale of five. The results showed that the smart box media from the material and appearance according to the expert (expert judgment) was in the